ASSOCIATION BETWEEN LEVEL OF FATIGUE AND PHYSICAL ACTIVITY OF POST-COVID-19 SURVIVORS AMONG IIUM KUANTAN COMMUNITY - ABDUL RAHMAN, ROZLIN; BT. SEJARI, AFIFAH SUHAILA (International Journal of Allied Health Sciences, 2023)
Introduction: Post-COVID-19 fatigue is symbolic in discussing long COVID. The new emergence of barriers might cause a deterioration in physical activity levels. Objective: This study aims to address the level of fatigue in post-COVID-19 survivors among the International Islamic University Malaysia (IIUM) Kuantan community and its association with the level of physical activity. Method: A cross-sectional study design was conducted on 75 IIUM Kuantan communities using a convenience sampling method based on the inclusion and exclusion criteria. All respondents answered a questionnaire on the demographic data, Fatigue Severity Scale (FSS) and a short-form version of the International Physical Activity Questionnaire (IPAQ-SF). Descriptive statistics, independent t-test and Chi-square test were applied to analyze the data. Result: The mean age of the respondents is 23.64±5.795, with an average mean score of FSS 4.242 (SD=1.097). The result shows a significant difference (p<0.001) between low and high fatigue groups with a high prevalence in the latter group. Gender (p=0.176) and recovery period post-COVID-19 (p=0.175) were not associated with fatigue levels. The result of the association between fatigue and physical activity level showed no significant relationship present, with a p-value of 0.703. Conclusion: Although there was no association found between fatigue and the physical activity level, the IIUM Kuantan post-COVID-19 community did experience high fatigue. Future prevention can target the correct populations and bring more research on fatigue with other factors such as quality of life (QoL) and functional status.